A Hybrid Expert System for Faulted Section Identification, Fault Type Classification and Selection of Fault Location Algorithms - Girgis, Adly A.; Johns, Melisa B. (IEEE power engineering review, 1989)
This paper presents an expert system developed in turbo prolog to identify faulted sections and interpret protective apparatus operation in large interconnected power systems. The expert system presented here is capable of identifying bus faults, line fault sections, and fault sections in the common area of a specific bus and line. Also, the expert system identifies relays or breakers malfunctions. The expert system is then expanded to include real-time measurements of current and voltage phasors to classify the type of fault that the faulted section has experienced. Furthermore, when the faulted section is a transmission line, the expert system selects an appropriate fault location algorithm to compute the fault location in miles. This paper shows that the combination of numeric and data base algorithm is essential to many developments in expert system application in power systems. Evaluating the expert systems reported so far for fault diagnosis reveals that all of these schemes utilize only the data received from breaker and relay status. Consider the recent trend in digital protection, real-time phasor measurements would be available. To combine real-time phasor measurements with relay and breaker status, a hybrid expert system is required. A hybrid expert system combines numeric algorithms with data base algorithms in one scheme. This paper recognizes this feature in the expert system developed here. The expert system reported in this paper includes four stages. The first stage determines the faulted section of the power system and reports correct and incorrect breaker and relay operation.